Size and Performance: Evidence on Brazilian Multimarket Funds (Global Journal of Management and Business Research, 2017)
This study aims to evaluate the effect of size on performance of Brazilian multimarket funds. The final sample is comprised by 231 funds covering 7,997 monthly observations in the period from January, 2009 to March, 2014. We employed multivariate regression analysis, with pooled data. Our research model also includes the following control variables: management fee, performance fee, and age. The main results show that size represents an important variable to address performance of investment funds in Brazil, and there are arguments about an optimal size for funds that operate in this market.
Keywords: hedge funds; latin america; emerging economies; finance; developing countries